Occupation-focused health promotion for well older people — A cost-effectiveness analysis. (March 2016) - Zingmark, Magnus; Nilsson, Ingeborg; Fisher, Anne G; Lindholm, Lars
Introduction: The aim of this study was to evaluate three occupational therapy interventions, focused on supporting continued engagement in occupation among older people, to determine which intervention was most cost effective, evaluated as the incremental cost/quality adjusted life year gained. Method: The study was based on an exploratory randomized controlled trial. Participants were 77–82 years, single living and without home help. One hundred and seventy seven persons were randomized to an individual intervention, an activity group, a discussion group or a no intervention control group. All interventions focused on supporting the participants to maintain or improve occupational engagement. Outcomes were evaluated at baseline, three and 12 months and included general health and costs (intervention, municipality and health care). Based on linear regression models, we evaluated how outcomes had changed at each follow-up for each intervention group in relation to the control group. Results: Both group interventions resulted in quality adjusted life years gained at three months. A sustained effect on quality adjusted life years gained and lower total costs indicated that the discussion group was the most cost-effective intervention. Conclusion: Short-term, occupation-focused occupational therapy intervention delivered in group formats for well older people resulted in quality-adjusted life years gained. A one-session discussion group was most cost effective.